Peran Lembaga Seniman Budayawan Muslimin Indonesia (LESBUMI) Jawa Barat dalam Mengoptimalkan Kegiatan Dakwah - Fauzi, Ahmad; Muhyiddin, Asep; Mujib, Abdul (Tadbir: Jurnal Manajemen Dakwah, 2025)
This research aims to understand the role of the Lembaga Seniman Budayawan Muslimin Indonesia (LESBUMI) PWNU in West Java in integrating art and culture into dawah. The study identifies challenges and opportunities in dawah efforts, including technological advancements and social changes. Art and culture can create profound experiences and enhance understanding of religion. Therefore, this research attempts to explain how LESBUMI PWNU in West Java plays a role in strengthening the relationship between art, culture, and dawah to achieve broader goals of enlightening and inspiring society. This research is also significant in promoting interfaith harmony and cultural diversity in Indonesia, especially in culturally and religiously rich regions like West Java. In the era of technology and globalization, art and culture continue to play a crucial role in conveying the message of dawah. This study will provide a deeper understanding of how art and culture can be effectively utilized to propagate religious teachings and bring about positive changes in society.